Increased densities of monocarboxylate transport protein MCT1 after chronic administration of nicotine in rat brain - Canis, Martin; Mack, Brigitte; Gires, Olivier; Maurer, Martin H.; Kuschinsky, Wolfgang; Dümbgen, Lutz; Duelli, Roman (Neuroscience research, 2009)
Chronic administration of nicotine is followed by a general stimulation of brain metabolism that results in a distinct increase of glucose transport protein densities for Glut1 and Glu3, and local cerebral glucose utilization (LCGU). This increase of LCGU might be paralleled by an enhanced production of lactate. Therefore, the question arose as to whether chronic nicotine infusion is accompanied by increased local densities of monocarboxylate transporter MCT1 in the brain. Secondly, we inquired whether LCGU might be correlated with local densities of MCT1 during normal conditions and after chronic nicotine infusion. Nicotine was given subcutaneously for 1 week by osmotic mini-pumps and local densities of MCT1 were measured by immunoautoradiographic methods in cryosections of rat brains. MCT1 density was significantly increased in 21 of 32 brain structures investigated (median increase 15.0±3.6%). Immunohistochemical stainings of these substructures revealed an over-expression of MCT1 within endothelial cells and astrocytes of treated animals. A comparison of 23 MCT1 densities with LCGU measured in the same structures in a previous study revealed a partial correlation between both parameters under control conditions and after chronic nicotine infusion. 10 out of 23 brain areas, which showed a significant increase of MCT1 density due to chronic nicotine infusion, also showed a significant increase of LCGU. In summary, our data show that chronic nicotine infusion induces a moderate increase of local and global density of MCT1 in defined brain structures. However, in terms of brain topologies and substructures this phenomenon did partially match with increased LCGU. It is concluded that MCT1 transporters were upregulated during chronic nicotine infusion at the level of brain substructures and, at least partially, independently of LCGU.
Online verfügbar: 9. Mai 2009
Gesehen am 13.01.2025